DERAJAT FUNGSI MOTORIK KASAR DENGAN EPILEPSI PADA ANAK DENGAN PALSI SEREBRAL - Yurika Elizabeth Susanti; Marcelina Pepita Kristiono; Arvin Leonard Sumadi Jap; Gratianus Billy Himawan; Muhammad Rifqi Khairi; Nurul Hidayah (Bahasa Indonesia, 2025)
Introduction: Epilepsy is a common comorbidity of cerebral palsy (CP). Variations in gross motor function affect functional outcomes in CP children significantly. This study aims to analyze the association between gross motor function and epilepsy in children with CP. Methods: A cross-sectional study was performed at the Pediatric Inpatient Ward, Outpatient Clinic, and Medical Rehabilitation Installation at Ulin General Hospital in Banjarmasin from July to September 2024. The subjects of the study were children between the ages of 2 and 18 who had been diagnosed with CP. We evaluated gross motor function utilizing the Gross Motor Function Classification System (GMFCS), categorizing the results into two groups: mild-moderate (GMFCS I-III) and severe (GMFCS IV-V) motor dysfunction. Chi-Square test was used for statistical analysis. Results: The study involved a total of 42 subjects diagnosed with CP. Twenty-eight subjects (66.7%) had epilepsy as a comorbidity. Twenty-three subjects experienced generalized seizures (82.1%), and 18 subjects were quadriplegic (64.3%). There were 17 subjects (40.5%) with mild-moderate motor dysfunction and 25 subjects (59.5%) with severe motor dysfunction. Twenty subjects with epilepsy showed severe motor dysfunction (71.4%). A significant association was identified between severe gross motor function and epilepsy in children with CP (p=0.026). Conclusion: Epilepsy was found to be significantly associated with cerebral palsy in children with severe gross motor dysfunction.